What did the pandemic teach us about effective health communication? Unpacking the COVID-19 infodemic - Eric J. Cooks; Melissa J. Vilaro; Brenda W. Dyal; Shu Wang; Gillian Mertens; Aantaki Raisa; Bumsoo Kim; Gemme Campbell-Salome; Diana J. Wilkie; Folake Odedina; Versie Johnson-Mallard; Yingwei Yao; et al. (BMC, 2022)
Abstract Background The spread of unvetted scientific information about COVID-19 presents a significant challenge to public health, adding to the urgency for increased understanding of COVID-19 information-seeking preferences that will allow for the delivery of evidence-based health communication. This study examined factors associated with COVID-19 information-seeking behavior. Methods An online survey was conducted with US adults (N = 1800) to identify key interpersonal (e.g., friends, health care providers) and mediated (e.g., TV, social media) sources of COVID-19 information. Logistic regression models were fitted to explore correlates of information-seeking. Results Study findings show that the first sought and most trusted sources of COVID-19 information had different relationships with sociodemographic characteristics, perceived discrimination, and self-efficacy. Older adults had greater odds of seeking information from print materials (e.g., newspapers and magazines) and TV first. Participants with less educational attainment and greater self-efficacy preferred interpersonal sources first, with notably less preference for mass media compared to health care providers. Those with more experiences with discrimination were more likely to seek information from friends, relatives, and co-workers. Additionally, greater self-efficacy was related to increased trust in interpersonal sources. Conclusion Study results have implications for tailoring health communication strategies to reach specific subgroups, including those more vulnerable to severe illness from COVID-19. A set of recommendations are provided to assist in campaign development.